PENGARUH KOMITMEN ORGANISASI, QUALITY OF WORK LIFE (QWL) TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR (OCB) DAN KINERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BANGKALAN MADURA JAWA TIMUR - Sumiati Sumiati; I Dewa ketut Raka Ardiana; Auliya Ika Pratiwi (Universitas 17 Agustus 1945 Surabaya, 2018)
The purpose of this research is to find the influence of commitment organization andquality of work life (qwl) of organizational citizenship behavior (ocb) and performanceemployees in city population civil Bangkalan Madura. The use of population and civil recorddistrict Bangkalan Madura as the study was based because of population and civil recordbangkalan the district madura as the public service known has employees who works lessmaximum.This research included in the kind of research quantitative the testing of hypotheses andquestionnaires as a technique of data collection. But as for an instrument it is anticipated thatanalysis in this research that is using structural equation model (sem). A population that inyou wherever you may be been disclosed in the research it is a whole employees of the citypopulation and civil registration kabupaten Bangkalan Madura a number of 109 civil servantsthat they employ .The results of the study based on the validity and reabilitas shows that data is valid andreliable. Based on the results of the hypothesis shows that; 1) a variable commitmentorganization significant on variables organizational citizenship behavior (ocb), 2) a variablecommitment organization significant on variables performance employees, 3) a variablequality of work life (qwl) significant on variables organizational citizenship behavior (ocb),4) a variable quality of work life (qwl) significant on variables performance employees, and5) a variable organizational citizenship behavior (ocb) significant on variables performanceemployees in city population civil district Bangkalan Madura .Keywords : Commitment organization, quality of work life (qwl), organizationalcitizenship behavior (OCB), and performance.